Health technology assessment : using biostatistics to break the barriers of adopting new medicines - Hopkins, Robert B.; Goeree, Ron (Boca Raton, Florida : CRC Press, 2015)
The term health technology refers to drugs, devices, and programs that can improve and extend quality of life. As decision-makers struggle to find ways to reduce costs while improving health care delivery, health technology assessments (HTA) provide the evidence required to make better-informed decisions. This is the first book that focuses on the statistical options of HTAs, to fully capture the value of health improvements along with their associated economic consequences. After reading the book, readers will better understand why some health technologies receive regulatory or reimbursement approval while others do not, what can be done to improve the chances of approval, as well as common shortcomings of submissions for drug and device reimbursement. The book begins by contrasting the differences between regulatory approval and reimbursement approval. Next, it reviews the principles and steps for conducting an HTA, including the reasons why different agencies will have a different focus for their scope in the HTA. Supplying an accessible introduction to the various statistical options for different methods in an HTA, the book identifies the links to regulatory and reimbursement decisions for each option. It highlights many of the methodological advances that have occurred since HTA research began, to provide researchers and decision-makers with a cutting-edge framework. It also details the logical basis for the methods along with simple instructions on how to conduct the various techniques. Both authors have considerable experience in generating evidence for submissions and reviewing submissions to decision-makers for funding. One of the authors has also received a nationally recognized lifetime achievement award in this area.
1.Regulation, reimbursement and health technology assessment -- 2.Requirements and sources of data to complete an HTA -- 3.Meta-analysis -- 4.Network meta-analysis -- 5.Bayesian methods -- 6.Survival analysis -- 7.Costs and cost of illness studies -- 8.Health-related quality of life -- 9.Missing data methods -- 10.Concluding remarks.
Includes bibliographical references and index.
Keywords: BIOMEDICAL TECHNOLOGY